2018
DOI: 10.3390/cryst8110403
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Nucleation and Growth Kinetics for Aqueous L-glycine Solutions from the Turbidity Induction Time Data

Abstract: As the turbidity induction time measurements are influenced by the size distribution of the nuclei at the detection point, these data should provide important information on both nucleation and growth. A model is developed in this work to determine the nucleation and growth kinetics of aqueous L-glycine solutions using the turbidity induction time data for various supersaturations from 293.15 K to 313.15 K. The photomicroscopic growth experiments of aqueous L-glycine solutions are also conducted to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
5
16
0
Order By: Relevance
“…As the intermediate value, f V = 4 × 10 −4 , was adopted at the detection of the nucleation point for the Lasentec focus beam reflectance measurements reported by Lindenberg and Mazzotti [32] and for the turbidity measurements reported by Shiau and Lu [28], this value was also adopted in this study. Based on f V = 4 × 10 −4 for spherical nuclei with L d = 10 µm and k V = π 6 , it leads to f N = 7.64 × 10 11 m −3 [30]. Figure 2 shows the increase of J J 0 with increasing S for the solutions without inhibitors at 37 • C, where J 0 represents the nucleation rate for S = 13.65.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the intermediate value, f V = 4 × 10 −4 , was adopted at the detection of the nucleation point for the Lasentec focus beam reflectance measurements reported by Lindenberg and Mazzotti [32] and for the turbidity measurements reported by Shiau and Lu [28], this value was also adopted in this study. Based on f V = 4 × 10 −4 for spherical nuclei with L d = 10 µm and k V = π 6 , it leads to f N = 7.64 × 10 11 m −3 [30]. Figure 2 shows the increase of J J 0 with increasing S for the solutions without inhibitors at 37 • C, where J 0 represents the nucleation rate for S = 13.65.…”
Section: Resultsmentioning
confidence: 99%
“…For simplicity, the induction time at a constant supersaturation level is often assumed to correspond to a point at which the total number density of the nuclei has reached a certain value, f N , in the induction time measurements [26][27][28][29][30]. Thus, one can derive, at the induction time t i ,…”
Section: Resultsmentioning
confidence: 99%
“…This observation can again be explained by the effect of saturation on the nucleation rate per Equation (3), and to a greater importance, on the growth rate. Higher concentration leads to higher S, which causes a higher rate of nucleation and growth [32]. At a higher saturation level, a greater extent of the polymer tends to precipitate out of the solution phase, which provides the required NP building units for the nuclei to growth.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the study of 28 inorganic systems, Mersmann and Bartosch [34] concluded that the minimum detectable volume fraction of nuclei in solution corresponds to f V = 10 −4 − 10 −3 with the minimum detectable size of 10 − 100 µm. The intermediate value, f V = 4 × 10 −4 , was adopted at the detection of the nucleation point for the Lasentec focus beam reflectance measurements reported by Lindenberg and Mazzotti [35] and for the turbidity measurements reported by Shiau et al [31][32][33]36]. If the uniform-sized spherical nuclei of 10 µm with k V = π 6 are assumed for simplicity, f V = 4 × 10 −4 corresponds to f N = 7.64 × 10 11 m −3 [32].…”
Section: Linearized Integral Methodsmentioning
confidence: 99%